A Cascade of Wnt, Eda, and Shh Signaling Is Essential for Touch Dome Merkel Cell Development. - Ying Xiao; Ying Xiao; Daniel T Thoresen; Lingling Miao; Jonathan S Williams; Chaochen Wang; Radhika P Atit; Sunny Y Wong; Isaac Brownell (PLoS Genetics)
The Sonic hedgehog (Shh) signaling pathway regulates developmental, homeostatic, and repair processes throughout the body. In the skin, touch domes develop in tandem with primary hair follicles and contain sensory Merkel cells. The developmental signaling requirements for touch dome specification are largely unknown. We found dermal Wnt signaling and subsequent epidermal Eda/Edar signaling promoted Merkel cell morphogenesis by inducing Shh expression in early follicles. Lineage-specific gene deletions revealed intraepithelial Shh signaling was necessary for Merkel cell specification. Additionally, a Shh signaling agonist was sufficient to rescue Merkel cell differentiation in Edar-deficient skin. Moreover, Merkel cells formed in Fgf20 mutant skin where primary hair formation was defective but Shh production was preserved. Although developmentally associated with hair follicles, fate mapping demonstrated Merkel cells primarily originated outside the hair follicle lineage. These findings suggest that touch dome development requires Wnt-dependent mesenchymal signals to establish reciprocal signaling within the developing ectoderm, including Eda signaling to primary hair placodes and ultimately Shh signaling from primary follicles to extrafollicular Merkel cell progenitors. Shh signaling often demonstrates pleiotropic effects within a structure over time. In postnatal skin, Shh is known to regulate the self-renewal, but not the differentiation, of touch dome stem cells. Our findings relate the varied effects of Shh in the touch dome to the ligand source, with locally produced Shh acting as a morphogen essential for lineage specification during development and neural Shh regulating postnatal touch dome stem cell maintenance.